Ponsel Lebih dari Sekedar Alat Komunikasi - Danu Widhyatmoko (Bina Nusantara University, 2011)
Cellular phone or mobile phone is a telecommunication device extremely consumed by all levels of society in Indonesia. Article presents a reality that mobile phone is not only communication devices. The presentation begins with the history of cell phones, both globally and also by the time of entering and growing in Indonesia. Then will also be discussed whether cell phones are being used properly according to their purpose and benefit by the Indonesian users. Moreover, whether cell phones can be the symbol of the users. Research method used in this paper is literature study, continued with reflective data analysis. It can be concluded that a more comprehensive picture of cultural development in society as a result of cell phones growth in Indonesia will be obtained. (DW)